An Analysis of the Maqashid al-S An Analysis of the Maqashid al-Shariah in Hadith Concerning Hybrid Contracts as an Instrument of Productive Philanthropy for Achieving Poverty Alleviation (SDG 1) - Fathoni, Ahmad Iqbal Fathoni; M. Zikwan (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to formulate a productive philanthropic model by integrating hadith with the Hybrid Contract concept in Islamic jurisprudence (fiqh muamalah), utilizing the maqashid shariah approach as a framework for economic empowerment and poverty alleviation aligned with Sustainable Development Goal 1. Employing a qualitative method, the research applies literature-based analysis, textual interpretation of hadith, and normative inquiry into the legal structure of hybrid contracts in Islamic financial practice. The findings indicate that combining prophetic values, shariah objectives, and contractual flexibility offers a productive philanthropy scheme that transcends consumptive aid. This model enhances the adaptability and sustainability of Islamic social finance mechanisms. The study underscores the necessity of policy reform in managing zakat, infaq, and waqf to be more economically empowering, encouraging a paradigmatic shift from passive distribution toward active, shariah-driven empowerment.